Integrasi Hukum Adat dan Hukum Negara di Indonesia: Perspektif Mazhab Sejarah Hukum dalam Konteks Sosial Legal Pada Pembangunan Ibu Kota Nusantara IKN - Gunawan, Abraham; Rohmatilah, Roudoh; Nurrahma Hartanty, Aissha; Laras Dewi Prasasti, Rr Novaryana; Rahman, Aisyah (UNES Law Review, 2024)
The integration of customary law and state law in Indonesia is a major challenge in a complex and diverse legal context. This research examines the dynamics of such integration using the school of legal history approach, which highlights the role of history in shaping these two legal systems and their implications for the social and legal life of society. The study analyzes the development of customary law and state law from the past to the present, identifying common ground and potential conflicts between the two. Using quantitative methods and a literature review, this study investigates the integration of customary and state law in Indonesia. This research provides an in-depth understanding of the dynamics of customary law and state law and their implications for future legal policy. The results are expected to make a significant contribution in designing more effective and inclusive policies to support social harmony and legal justice in Indonesia.